2022
DOI: 10.1002/anie.202202491
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Doubly‐Strapped Isolated Perylene Diimide Chromophore

Abstract: Perylene diimides (PDIs), a well-studied class of organic dyes, have a strong tendency to self-aggregate in water, thus greatly restricting their phototheranostic applications. Herein, we report a water-soluble PDI cyclophane "Gemini Box" (GBox-1 4 + ), consisting of a central PDI chromophore enclosed by double-sided cationic molecular straps. Owing to the effective spatial isolation, the chromophore self-aggregation can be completely eliminated, even in a concentrated aqueous solution up to 2 mM. To our knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…In the control group without laser irradiation at 808 nm, only 12.9 % of Escherichia coli were killed due to the inherent antibacterial activity of the proton‐inclined pyridine group in BPCA‐S‐UV (Figure S46) [23] . It should be noted that this is the first small molecule photothermal conversion system functioning with the synergetic participation of protons and electrons, which is different from previous systems designed by the incorporation of an NIR‐absorbing organic molecule or performed with the formation of free radicals after a single electron‐transfer reaction [21a,c] . Given the diverse proton‐containing groups of the basic ingredients in bodily tissue, such a proton/electron coupling strategy can be a promising alternative to further promote photothermal therapy for disease through target hydrogen‐bonding recognition after optimizing the triggering temperature with a proper proton acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…In the control group without laser irradiation at 808 nm, only 12.9 % of Escherichia coli were killed due to the inherent antibacterial activity of the proton‐inclined pyridine group in BPCA‐S‐UV (Figure S46) [23] . It should be noted that this is the first small molecule photothermal conversion system functioning with the synergetic participation of protons and electrons, which is different from previous systems designed by the incorporation of an NIR‐absorbing organic molecule or performed with the formation of free radicals after a single electron‐transfer reaction [21a,c] . Given the diverse proton‐containing groups of the basic ingredients in bodily tissue, such a proton/electron coupling strategy can be a promising alternative to further promote photothermal therapy for disease through target hydrogen‐bonding recognition after optimizing the triggering temperature with a proper proton acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…We simultaneously reacted a small amount of Co and Zn with 2‐methylimidazole (Co 2+ and Zn 2+ were coordinated with the same sodalite of 2‐methylimidazole) [the molar ratio of Zn/Co precursor was 50 : 1] and successfully fabricated the Zn and Co bimetal metal‐organic framework (CoZn@BMOF) with a uniform elemental distribution. Through high‐temperature pyrolysis, the Zn atoms in the material were evaporated, and Co with a high boiling point was reduced by the Zn vapour and stabilised by the N atoms in the MOFs, thus forming a classic and stable low‐valent single‐atom Co−N−C catalyst (Co 1 −N 4 @NC, Figure 1c) [45–50] . We used p ‐toluoyl chloride as the substrate and carried out fluorination under the classical reaction conditions developed by Baker's group to verify the catalytic activity of the low‐valent Co 1 −N 4 @NC SAC [23] .…”
Section: Resultsmentioning
confidence: 99%
“…Through high-temperature pyrolysis, the Zn atoms in the material were evaporated, and Co with a high boiling point was reduced by the Zn vapour and stabilised by the N atoms in the MOFs, thus forming a classic and stable low-valent single-atom CoÀ NÀ C catalyst (Co 1 À N 4 @NC, Figure 1c). [45][46][47][48][49][50] We used p-toluoyl chloride as the substrate and carried out fluorination under the classical reaction conditions developed by Baker's group to verify the catalytic activity of the low-valent Co 1 À N 4 @NC SAC. [23] The experimental results showed that Co 1 À N 4 @NC can successfully catalyse fluorination between excess AgF (2.5 equivalent) and p-toluoyl chloride, resulting in the almost quantitative generation of the target acyl fluoride product.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the CT paradigm of cocrystals, many cyclophane hosts, acting as either donors or acceptors, are capable of binding electronically complementary guest molecules to form colored host–guest CT complexes [27–35] . These host–guest cyclophane systems with high light‐absorption activity are ideal candidates as PTAs, which could be endowed with some unique advantages including i) molecular‐level well‐defined structure and uniform chemical composition favorable for more precise therapy, ii) high water solubility and good biocompatibility available for biological systems without additional surface modification, and iii) controllable light‐harvesting capacity by easily changing guest components.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the CT paradigm of cocrystals, many cyclophane hosts, acting as either donors or acceptors, are capable of binding electronically complementary guest molecules to form colored host-guest CT complexes. [27][28][29][30][31][32][33][34][35] These host-guest cyclophane systems with high lightabsorption activity are ideal candidates as PTAs, which could be endowed with some unique advantages including i) molecular-level well-defined structure and uniform chemical composition favorable for more precise therapy, ii) high water solubility and good biocompatibility available for biological systems without additional surface modification, and iii) controllable light-harvesting capacity by easily changing guest components. Although some host-guest complexes involving radical-radical interaction [36] or activated guests [37][38] have shown NIR photothermal effect, the simple electron donor-acceptor CT absorption in host-guest cyclophane systems has rarely been exploited for NIR photothermal therapy, [39] particularly for NIR-II photoablation, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%